Perilaku Konsumtif Gaya Hidup Santri Prespektif Ekonomi Islam: (Studi Kasus Santri Amtsilati Pondok Pesantren Syaichona Moh. Cholil Putri) - Ihsan Ihsan; Mukrimah Mukrimah (Journal of Economic and Islamic Research, 2023)
Consumption is a resource that is needed by humans in everyday life which produces satisfaction for them. However, consumption here has several requirements that must be met, namely consuming good (halal) goods, being thrifty, not being extravagant, avoiding debt, avoiding stinginess and stinginess so that it does not result in behavior in consuming goods with israf. The purpose of this research is to analyze the form of Consumptive Behavior of Santri Amtsilati Pondok Pesantren Syaichona Moh. Cholil Putri Bangkalan. The research method used by the author is a qualitative method with research subjects of students and teachers. The method of collecting data in this study is using interviews, observation, and documentation. The results showed that the consumptive behavior of Amtsilati students at Syaichon Moh Islamic Boarding School. The Cholil daughters they have are different and there are various types of consumers who are consumptive in terms of food, skincare and clothing. So from the results of this study it was found that the lifestyle behavior of Amtsilati students tends to behave consumptively or extravagantly so that their consumptive nature results in high consumptive, moderate consumptive, and low consumptive categories and this is not justified in Islam.